Editor's message: beaming energy from the space - Aguilar Garib, Juan Antonio (2017)
Our society is consuming energy figures which are so large that sometimes they become meaningless when mentioned; electricity alone in 2012 was 20,900 TWH (IEA World energy statistics), 68% from fossil fuels, 11% nuclear and 21% ‘renewable’; the energy that comes from resources that are not significantly depleted by their use, such as sunlight, wind, rain, tides, waves and geothermal heat. It is estimated that energy consumed in the buildings (residential and commercial end users) accounts for 20.1% of this total ([International Energy Outlook 2016). Losses are not considered here, but they are not negligible, either.